Censurae Librorum - Olszewski, Lechosław (Polskie Towarzystwo Filologiczne, 2020)
Paweł Sawiński, The Succession of Imperial Power under the Julio-Claudian Dynasty (30 BC–AD 68), Berlin: Peter Lang, 2018, 298 pp., 28 figures, ISBN 978-3-631-75773-4, €53.90.Oliver Hekster, Emperors and Ancestors: Roman Rulers and the Constraints of Tradition, Oxford: Oxford University Press, 2015 (Oxford Studies in Ancient Culture and Representation),XXXII + 395 pp., 109 figures, 5 tables, ISBN 978-0-19-873682-0, ₤110.00.